2020
DOI: 10.1021/acscatal.9b05154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen Mobility in La–Fe-Based Perovskites on the Catalytic Activity and Selectivity of Methane Oxidation

Abstract: The mechanism and structure requirements of selective and total oxidation of methane in a chemical looping process are both experimentally and theoretically examined on La 1−x Sr x FeO 3−δ (x = 0, 0.2, and 0.5) and La 0.5 Sr 0.5 Fe 1−x Co x O 3−δ (x = 0.5 and 1) perovskites. The oxygen mobility in the perovskites described by the formation energy of oxygen vacancy is found to have a pronounced effect on the catalytic activity and selectivity. In particular, the selectivity is controlled largely by the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 66 publications
10
93
0
Order By: Relevance
“…examined the reactivity of La 1‐x Sr x FeO 3‐δ (x=0, 0.2, and 0.5) and La 0.5 Sr 0.5 Fe 1‐x Co x O 3‐δ (x=0.5 and 1) perovskites for CLR of CH 4 and found that CO selectivity decreased from 92 % to 9 %, whereas the reducible ability promoted greatly with Sr and Co substitution resulted from Fe 4+ or oxygen vacancies formed. By the combination of experimental results and theoretical calculations, the authors established a quantitative relationship between bulk oxygen (O b ), surface oxygen concentration (O s ) and oxygen mobility which was associated with the relative ratio of the surface reactions rate to the diffusion rate of the lattice oxygen measured by Φ and Φ′values, as shown in Figure 9 [48b] . O s decreased with reduced oxygen mobility (a higher Φ and Φ′values) at the fixed O b thus preferred the partial oxidation and vice versa thus benefited total oxidation of methane.…”
Section: Oxygen Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…examined the reactivity of La 1‐x Sr x FeO 3‐δ (x=0, 0.2, and 0.5) and La 0.5 Sr 0.5 Fe 1‐x Co x O 3‐δ (x=0.5 and 1) perovskites for CLR of CH 4 and found that CO selectivity decreased from 92 % to 9 %, whereas the reducible ability promoted greatly with Sr and Co substitution resulted from Fe 4+ or oxygen vacancies formed. By the combination of experimental results and theoretical calculations, the authors established a quantitative relationship between bulk oxygen (O b ), surface oxygen concentration (O s ) and oxygen mobility which was associated with the relative ratio of the surface reactions rate to the diffusion rate of the lattice oxygen measured by Φ and Φ′values, as shown in Figure 9 [48b] . O s decreased with reduced oxygen mobility (a higher Φ and Φ′values) at the fixed O b thus preferred the partial oxidation and vice versa thus benefited total oxidation of methane.…”
Section: Oxygen Carriersmentioning
confidence: 99%
“… Relationship among [O s ], [O b ], Φ and Φ′ at (a) partial oxidation and (b) Total oxidation dominating [48b] . Reproduced with permission from Ref.…”
Section: Oxygen Carriersmentioning
confidence: 99%
“…The oxygen in the gas phase can be activated by the surface chemical oxygen on the catalyst's surface, it can facilitate the oxidation of NO to NO 2 and thus accelerating the CO-SCR process [16,[44][45][46]. Chang et al [20] studied the surface properties of LaFeO 3 perovskite catalysts. They reported that the peak with the lowest binding energy between 527 and 531 eV was attributed to the lattice O species, whereas the chemisorbed O or OH − or hydroxides species, and particularly adsorbed water species were observed at the highest binding energies between 530 and 536 eV.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…However, the mono iron catalyst shows weak catalytic activity for NO removal at low temperatures [19]. Chang et al [20] and Mihai et al [21] reported that the concentration of oxygen vacancies on the LaFeO 3 perovskite catalyst's surface is strongly related to the bulk oxygen concentration and the relative diffusion rate of the lattice oxygen with respect to the surface reaction. They found that the partial replacement of La with Sr at the A-site, and partial replacement of Fe with Co or Mn at the B-site of the ABO 3 perovskite, caused an increase in the surface oxygen vacancies and oxygen mobility, which can affect the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 The ABO 3 perovskites has been reported to catalyse oxidation reactions due to their unique properties such as flexibility of crystal structure and tuneable electronic properties. 30 These include use as supports for active metal species, substitution of either the A or B site of the ABO 3 perovskites. The La-based inorganic perovskites are inexpensive and readily available.…”
Section: Introductionmentioning
confidence: 99%